The Attractiveness 0f Sharia Financial Institutions for MSMEs in Pontianak City, The Province of West Kalimantan, Indonesia - Massardi, Restiatun; Kapriana, Angga Permadi; Apriyani, Apriyani (IQTISHADIA, 2021)
The development of Micro, Small and Medium Enterprises (MSMEs) requires support from financial institutions, both banking and non-banking, in providing working capital loans. This support includes ease of procedure, easy installment payments, and services. The contribution of Islamic financial institutions in the Province of West Kalimantan, Indonesia, cannot be ignored. This study aims to investigate determinants of the behavior in the selection of sharia financial institutions in Pontianak by MSMEs. The research samples were the perpetrators of MSMEs spread in six districts in Pontianak City, 20 MSMEs per district. The data in this study were the primary data obtained from a questionnaire survey. The data analysis technique used was Probit Regression Analysis. The results of this study indicate that the profit-sharing system that is considered not burdensome to customers, the simplicity of procedures that save time and cost, and the number of products offered in accordance with the customer needs significantly influence the probability of choosing Islamic financial institutions. The variable of the suitability of the operational rules of Islamic financial institutions with Islamic rules has no effect on customers’ decision in choosing a financial institution. This is an opportunity for Islamic financial institutions to develop their businesses by offering their products to non-Muslim customers.